i-StudentCare: Pembangunan Aplikasi Pengurusan Rutin Harian Diri bagi Pelajar UTHM Pagoh - Jofri, Hanif; Rahim, Razlan; Abdu, Iman; Hafiz, Harith Haikal (Multidisciplinary Applied Research and Innovation, 2023)
Self -management of daily routines is a necessity for every layer of society, especially for university students to improve the overall well -being of individuals, thus resulting in better productivity. Meanwhile, for students of Universiti Tun Hussein Onn Malaysia Pagoh branch, students need an application which is specially designed for students to manage flexible and balanced daily routines such as task scheduling and social life. The methodology used is the AGILE model. The application is self -tested. The survey was distributed to 15 respondents and we concluded that the application is very relevant to the current situation as hybrid classes are well known practice these day.